Tanezumab for chronic low back pain: a randomized, double-blind, placebo- and active-controlled, phase 3 study of efficacy and safety - Markman, John D.; Bolash, Robert B.; Mcalindon, Timothy E.; Kivitz, Alan J.; Pombo-Suarez, Manuel; Ohtori, Seiji; Roemer, Frank; Li, David J.; Viktrup, Lars; Bramson, Candace; West, Christine R.; Verburg, Kenneth M. (Pain, 2020)
This randomized, double-blind, phase 3 study (56-week treatment; 24-week follow-up) assessed tanezumab in patients with chronic low back pain and history of inadequate response to standard-of-care analgesics (NCT02528253). Patients received placebo, subcutaneous tanezumab (5 or 10 mg every 8 weeks), or oral tramadol prolonged-release (100-300 mg/day). Primary endpoint was change in low back pain intensity (LBPI) at week 16 for tanezumab vs placebo. Key secondary endpoints were proportion of patients with >= 50% decrease in LBPI at week 16, change in Roland Morris Disability Questionnaire at week 16, and change in LBPI at week 2 for tanezumab vs placebo. Adverse events and joint safety were assessed through weeks 56 and 80, respectively. Tanezumab 10 mg met the primary endpoint by significantly improving LBPI at week 16 vs placebo; least squares (LS) mean (95% CI) difference = -0.40 (-0.76 to -0.04;P= 0.0281). Tanezumab 10 mg significantly improved all key secondary endpoints. Tanezumab 5 mg did not meet the primary endpoint (LS mean [95% CI] treatment difference vs placebo = -0.30 [-0.66 to 0.07;P= 0.1117]), preventing formal testing of key secondary endpoints for this dose. The proportion of patients with >= 50% improvement in LBPI at week 16 was 37.4% in the placebo group, 43.3% in the tanezumab 5 mg group (Odds ratio [95% CI] vs placebo = 1.28 [0.97 to 1.70;P= 0.0846]), and 46.3% in the tanezumab 10 mg group (Odds ratio [95% CI] vs placebo = 1.45 [1.09 to 1.91;P= 0.0101]). Prespecified joint safety events were more frequent with tanezumab 10 mg (2.6%) than tanezumab 5 mg (1.0%), tramadol (0.2%), or placebo (0%). Seven patients, all in the tanezumab 10 mg group (1.4%), underwent total joint replacement. In conclusion, tanezumab 10 mg significantly improved pain and function vs placebo in patients with difficult-to-treat chronic low back pain. Tanezumab was associated with a low rate of joint safety events, some requiring joint replacement.
CRIS-Team WoS Importer:2020-10-09